2023
DOI: 10.1101/2023.04.25.538145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting Transferrin Receptor to Transport Antisense Oligonucleotides Across the Blood-Brain Barrier

Abstract: Antisense oligonucleotides (ASO) are promising therapies for neurological disorders, though they are unable to cross the blood-brain barrier (BBB) and must be delivered directly to the central nervous system (CNS). Here, we use a human transferrin receptor (TfR)-binding molecule to transport ASO across the BBB in mice and non-human primates, termed oligonucleotide transport vehicle (OTV). Systemically delivered OTV drives significant, cumulative, and sustained knockdown of the ASO target across multiple CNS re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The transport of oligonucleotide therapeutics such as ASOs across the blood–brain-barrier by Brainshuttle-mediated transcytosis has been confirmed as a promising approach for the delivery of ASOs to the CNS. As a recent example, Barker et al have demonstrated that brain concentrations of up to 30 nM of a Malat1 ASO after four IV injections in nonhuman primates (NHP) can be achieved …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The transport of oligonucleotide therapeutics such as ASOs across the blood–brain-barrier by Brainshuttle-mediated transcytosis has been confirmed as a promising approach for the delivery of ASOs to the CNS. As a recent example, Barker et al have demonstrated that brain concentrations of up to 30 nM of a Malat1 ASO after four IV injections in nonhuman primates (NHP) can be achieved …”
Section: Resultsmentioning
confidence: 99%
“…For example, the need to escape a lysosomal localization may reduce access to the target mRNA in the nucleus. While this could have general implications for the conjugate approach, in the in vivo setting, the presence of the BBB necessitates a Brainshuttle for targeted transport across this barrier as the ASO alone is not able to cross it in sufficient amounts …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are many hurdles to overcome before DGAT inhibition becomes a viable therapeutic or preventative option. These include achieving delivery across the blood brain barrier (a challenge which has promising solutions in antibody-mediated delivery 55 ) and correct dosing to avoid toxicity due to inhibition of the key fat storage functions of DGAT enzymes. This latter challenge could perhaps be overcome by exploiting functional redundancy of DGAT1 and DGAT2.…”
Section: Discussionmentioning
confidence: 99%